Hipertextualidad en Concierto barroco de Alejo Carpentier - Hernández Guerra, Ana María (2022)
From the concepts of hypertextuality, as one of the forms of transtextuality, raised by Gérard Genette, the novel Concierto barroco by Alejo Carpentier is analyzed, from the starting texts, or hypertexts, that originated them to the arrival texts, or hypotexts; and even the melodies that also inspired through another modality of hypertextuality called transmodalization. What is new in this article is the deepening of hypertextuality, as a specific form of intertextuality. This article is derived from the research of the Master’s thesis in Creative Writing that is presented in the Postgraduate Unit of the Faculty of Letters and Human Sciences of the National University of San Marcos.